Здатнiсть псевдокiльцевих тестiв виявляти динамiчнi одиночнi несправностi у словоорiєнтованiй пам’ятi - Gritcov, S. S.; Sorokin, G. F.; Shestacova, T. V. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
This paper presents single dynamic faults and methods for their detection. Such dynamic faults as dRDF, dDRDF and dIRF are considered in detail. Also, pseudo-ring testing and the principles of single dynamic faults detecting by pseudo-ring tests are considered. The paper presents the resolution determination results for pseudo-ring tests in relation to these faults in the word-oriented memory. Also, a comparative analysis of the pseudo-ring tests with known March tests is done. The results show that pseudo-ring tests with an algorithmic complexity of (30-60)N, where N is the number of all memory cells, can cover from 75 to 100% of all single dynamic faults. This advantage allows using pseudo-ring tests as an alternative to existing classical and March tests.